1999
DOI: 10.1152/ajpheart.1999.277.6.h2167
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACE inhibition and β-receptor blockade on energy metabolism in rats postmyocardial infarction

Abstract: Chronic treatment with beta-receptor blockers or angiotensin-converting enzyme (ACE) inhibitors in heart failure can reduce mortality and improve left ventricular function, but the mechanisms involved in their beneficial action remain to be fully defined. Our hypothesis was that these agents prevent the derangement of cardiac energy metabolism. Rats were subjected to myocardial infarction (MI) or sham operation. Thereafter, animals were treated with bisoprolol, captopril, or remained untreated. Two months late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
4
23
0
1
Order By: Relevance
“…These changes were in agreement with previous findings in experimental heart failure 5,6,8,9,[12][13][14] and in end-stage human heart failure, 15,16) and were characterized by a significant shift of cardiac CK isoenzymes towards the fetal BB-and MB-CK isoenzymes. This suggests a compensatory mechanism towards a more efficient cardiac CK system to improve cardiac energy metabolism in the LV dysfunctional condition.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These changes were in agreement with previous findings in experimental heart failure 5,6,8,9,[12][13][14] and in end-stage human heart failure, 15,16) and were characterized by a significant shift of cardiac CK isoenzymes towards the fetal BB-and MB-CK isoenzymes. This suggests a compensatory mechanism towards a more efficient cardiac CK system to improve cardiac energy metabolism in the LV dysfunctional condition.…”
Section: Discussionsupporting
confidence: 92%
“…23) A number of investigators reported changes in the cardiac CK system in chronic heart failure after experimental MI in rats, usually at 8 weeks after coronary ligation. 5,6,8,[10][11][12] These included reductions in total CK and mitochondrial CK activities and decreased total CR levels, as shown at 12 weeks after MI in the present study. In addition, a decreased mitochondrial CK fraction and increased MB-and BB-CK fractions were also characterized.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…15 Furthermore, in residual intact myocardium, PCr levels are reduced by up to 30% 15 and Flux CK up to 50%, 15 but ATP and P i levels remain constant. This HF model is well suited to study the effects of pharmacological intervention: eg, ACE inhibitors 18,22 and ␤-receptor blockers 22 have been found to preserve cardiac structure, function, and energetics, whereas the Ca 2ϩ channel blocker anipamil 23 exerted detrimental effects in this model.…”
Section: Definition Of the Modelmentioning
confidence: 99%
“…3,4 In contrast, the finding that estradiol-treated female rodents have a greater post-MI rate of death argues against a protective role. 5,6 Recent human studies on hormone replacement therapy similarly question the cardioprotective role of estrogen. 7,8 Clearly, the role of estrogen in cardiovascular disease (CVD) is complex, and further study is necessary.…”
mentioning
confidence: 99%